Application of polymer-based phase change materials in thermal safety management of power batteries. (25th November 2022) - Wang, Weixuan; Li, Chuanchang; Zeng, Xiaoliang; Chen, Jian; Sun, Rong
Abstract: With the gradual depletion of fossil energy, the development of electric vehicles has attracted more and more researchers' attention. As the core of the electric vehicle, high-performance power battery plays a very important role in its popularity and safety. However, the temperature control problem of power batteries has seriously restricted the development of electric vehicles. Too high or too low temperature will affect the service life of the battery. Therefore, the power battery can only work stably within an appropriate working range. This paper summarizes the methods to prevent the thermal runaway of the battery and analyzes the advantages of polymer-based phase change materials (PCMs) used in the battery thermal management system: the PCMs can play an obvious temperature control effect by using their phase change latent heat, and the addition of polymers solves the problem that the PCMs are easy to leak for a long time. The formation and thermal conductivity mechanism of polymer-based PCMs are reviewed. The addition of metal filler, carbon filler, and inorganic filler can improve the thermal conductivity of polymer-based PCMs. The main applications of polymer-based PCMs in BTMS are reviewed. Finally, some suggestions for its future development are put forward. Highlights: Summarizes the battery internal materials that can be used for BTM Different types of polymer-based form-stable PCMs that can be used for BTM are reviewed. The methods for improving the performance of polymer-based PCMs are summarized. The challenges of PCMs in leak-proof, flexibility, insulation and self-heating are presented.